Utilizing 3D fast spin echo anatomical imaging to reduce the number of contrast preparations in T 1 ρ $$ T_{1ρ } $$ quantification of knee cartilage using learning-based methods - Zhong, Junru; Huang, Chaoxing; Yu, Ziqiang; Xiao, Fan; Blu, Thierry; Li, Siyue; Ong, Tim-Yun Michael; Ho, Ki-Wai Kevin; Chan, Queenie; Griffith, James F; Chen, Weitian (Magnetic resonance in medicine, 2025)
To propose and evaluate an accelerated quantification method that combines -weighted fast spin echo (FSE) images and proton density (PD)-weighted anatomical FSE images, leveraging deep learning models for mapping. The goal is to reduce scan time and facilitate integration into routine clinical workflows for osteoarthritis (OA) assessment. This retrospective study utilized MRI data from 40 participants (30 OA patients and 10 healthy volunteers). A volume of PD-weighted anatomical FSE images and a volume of -weighted images acquired at a non-zero spin-lock time were used as input to train deep learning models, including a 2D U-Net and a multi-layer perceptron (MLP). maps generated by these models were compared with ground truth maps derived from a traditional non-linear least squares (NLLS) fitting method using four -weighted images. Evaluation metrics included mean absolute error (MAE), mean absolute percentage error (MAPE), regional error (RE), and regional percentage error (RPE). The best-performed deep learning models achieved RPEs below 5% across all evaluated scenarios. This performance was consistent even in reduced acquisition settings that included only one PD-weighted image and one -weighted image, where NLLS methods cannot be applied. Furthermore, the results were comparable to those obtained with NLLS when longer acquisitions with four -weighted images were used. The proposed approach enables efficient mapping using PD-weighted anatomical images, reducing scan time while maintaining clinical standards. This method has the potential to facilitate the integration of quantitative MRI techniques into routine clinical practice, benefiting OA diagnosis and monitoring.